Analysis of hepatitis B surface antigen (HBsAg) using high‐sensitivity HBsAg assays in hepatitis B virus carriers in whom HBsAg seroclearance was confirmed by conventional assays. Issue 3 (26th October 2017) - Ozeki, Itaru; Nakajima, Tomoaki; Suii, Hirokazu; Tatsumi, Ryoji; Yamaguchi, Masakatsu; Kimura, Mutsuumi; Arakawa, Tomohiro; Kuwata, Yasuaki; Ohmura, Takumi; Hige, Shuhei; Karino, Yoshiyasu; Toyota, Joji
Abstract : Aim: We investigated the utility of high‐sensitivity hepatitis B surface antigen (HBsAg) assays compared with conventional HBsAg assays. Methods: Using serum samples from 114 hepatitis B virus (HBV) carriers in whom HBsAg seroclearance was confirmed by conventional HBsAg assays (cut‐off value, 0.05 IU/mL), the amount of HBsAg was re‐examined by high‐sensitivity HBsAg assays (cut‐off value, 0.005 IU/mL). Cases negative for HBsAg in both assays were defined as consistent cases, and cases positive for HBsAg in the high‐sensitivity HBsAg assay only were defined as discrepant cases. Results: There were 55 (48.2%) discrepant cases, and the range of HBsAg titers determined by high‐sensitivity HBsAg assays was 0.005–0.056 IU/mL. Multivariate analysis showed that the presence of nucleos(t)ide analog therapy, liver cirrhosis, and negative anti‐HBs contributed to the discrepancies between the two assays. Cumulative anti‐HBs positivity rates among discrepant cases were 12.7%, 17.2%, 38.8%, and 43.9% at baseline, 1 year, 3 years, and 5 years, respectively, whereas the corresponding rates among consistent cases were 50.8%, 56.0%, 61.7%, and 68.0%, respectively. Hepatitis B virus DNA negativity rates were 56.4% and 81.4% at baseline, 51.3% and 83.3% at 1 year, and 36.8% and 95.7% at 3 years, among discrepant and consistent cases, respectively. Hepatitis B surface antigen reversion was observed only in discrepant cases. Conclusions: Re‐examination by high‐sensitivity HBsAg assays revealed that HBsAg was positive in approximately 50% of cases. Cumulative anti‐HBs seroconversion rates and HBV‐DNA seroclearance rates were lower in these cases, suggesting a population at risk for HBsAg reversion.